The science communication of formal gender studies: a comparative analysis - Stundžė, Lijana (Information & Media, 2018)
Science communication is important as it is a mean to inform the society about the problems discussed in science; it’s also necessary for scientists to learn about the way society understands their work and what are society’s expectations regarding it. The dissemination of scientific knowledge is also important for making informed decisions.Gender studies are a field of an interdisciplinary study devoted to issues of social injustice on levels both local and the global. It is a kind of science of civic engagement, which aims, among other things, to help to create a just social policy for both women and men.The aim of this article is to compare the various aspects of formal scientific communication in the science journal Gender Studies and Research, social science journals Sociologija. Mintis ir veiksmas, Filosofija. Sociologija, Socialiniai tyrimai, Socialinis darbas, Socialinių mokslų studijos, Tiltai and Acta paedagogica Vilnensia with formal science communication in the periodicals.This study includes the following dimensions of comparative analysis: topics of the publications, institutional affiliation of the authors of the articles, the leaders of science communication.An analysis of the topics of the articles in science journals and periodicals indicates the following most popular topics of research: NGO movements, gender roles and images in mass media and literature; gender and career; family issues. The only overlapping topic in the science journals and periodicals is education and science.The research of the publications of the journals and periodicals identified higher education and research institutions in Lithuania that conduct gender studies and disseminate their results. The main institutions that were most numerously represented in the journals and periodic were Vilnius University, Šiauliai University and Mykolas Romeris University. The most active researchers that published the most articles on gender studies in the journals were V. Šidlauskienėand A. Žvinklienė, and most active researchers in periodicals – M. A. Pavilionienė, O. Voverienė, G. Purvaneckienė, D. Šatkovskienė, V. Jurėnienė. It is obvious that the names of the scientists are different.It is worth noting that the effective dissemination of knowledge generated in gender studies is relevant not only for other researchers and the professional community, but that it could also be very valuable in the processes of law and decision-making as well as being used in initiatives for social, economic and political change.